2021
DOI: 10.1038/s41398-021-01669-0
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative neural signals predict rapid antidepressant effects of deep brain stimulation

Abstract: Deep brain stimulation (DBS) of the subcallosal cingulate (SCC) is a promising intervention for treatment-resistant depression (TRD). Despite the failure of a clinical trial, multiple case series have described encouraging results, especially with the introduction of improved surgical protocols. Recent evidence further suggests that tractography targeting and intraoperative exposure to stimulation enhances early antidepressant effects that further evolve with ongoing chronic DBS. Accelerating treatment gains i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…Additionally, the identification of oscillatory correlates during active stimulation may capture depression-salient brain dynamics present only during active stimulation drive, complementing recent results from our group [28, 47]. The observation of changes within the β range is consistent with other DBS indications [48] as well as with resting-state results from our own lab [47, 18]. The asymmetry observed aligns with asymmetries found in depression, though these typically involve frontal α , and with asymmetries evoked by SCCwm actions on brain networks [49].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Additionally, the identification of oscillatory correlates during active stimulation may capture depression-salient brain dynamics present only during active stimulation drive, complementing recent results from our group [28, 47]. The observation of changes within the β range is consistent with other DBS indications [48] as well as with resting-state results from our own lab [47, 18]. The asymmetry observed aligns with asymmetries found in depression, though these typically involve frontal α , and with asymmetries evoked by SCCwm actions on brain networks [49].…”
Section: Discussionsupporting
confidence: 75%
“…Explicit mismatch compression corrections enabled the use of hourly recordings sampled evenly across weeks, more regularly capturing symptoms probed by the HDRS17 [22, 24]. Additionally, the identification of oscillatory correlates during active stimulation may capture depression-salient brain dynamics present only during active stimulation drive, complementing recent results from our group [28, 47]. The observation of changes within the β range is consistent with other DBS indications [48] as well as with resting-state results from our own lab [47, 18].…”
Section: Discussionmentioning
confidence: 76%
“…Lastly, we applied TRAKR to an 8-channel neural time-series dataset recorded from the SCC of human patients (Figure 4). The overall goal of the recording protocol in the OR was to find neural signatures (or biomarkers) of behavioral effects observed in response to intraoperative brain stimulation ([34]; see subsubsection 2.5.2 for more details). For a particular individual, 8-channel recordings were obtained after stimulation on each contact (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…We also applied TRAKR to another neural dataset, 8-channel data recorded from the subcallosal cingulate (SCC) region of human patients with treatment-resistant depression who are undergoing deep brain stimulation in the operating room (OR) ([34, 36]). We found that TRAKR-derived reservoir activations can be used to better distinguish the effect of stimulation on neural patterns, achieving greater separation in latent space compared to raw traces.…”
Section: Introductionmentioning
confidence: 99%
“…Minocycline, which inhibits microglia activation, can prevent behavioral deficits induced by maternal immune activation, maternal sleep deprivation, and neonatal alcohol exposure in rodents [ 67 , 68 , 87 , 104 , 105 , 110 , 111 ]. Deep-brain stimulation is used as a therapeutic in human patients with mood and neuropsychiatric disorders [ 112 , 113 , 114 ]. In animal models, it was found that stimulation of the medial prefrontal cortex in MIA rats prevented behavioral and neuronal deficits [ 69 , 115 ].…”
Section: Developmental Stressors’ Impact On Brain Microgliamentioning
confidence: 99%